Understanding determinants of farmers’ investments in, and impacts of, soil and water conservation in Ethiopia: review and synthesis [Abstract only] - Adimassu, Zenebe; Langan, Simon J.; Johnston, Robyn M. (2015)
Although there has been a considerable effort to reduce soil erosion and improve land productivity in Ethiopia, farmers’ investments in SWC remain limited. There is a long and rich tradition of empirical research that seeks to identify the determinants that affect farmers’ investments in SWC practices. Nevertheless, the results regarding these determinants have been inconsistent and scattered. Moreover, the impacts of different SWC practices have not been reviewed and synthesized. Thus, this paper reviews and synthesizes past research in order to dentify determinants that affect farmers’ investments in SWC practices, and to also assess the impact of SWC practices within the framework of ecosystem services, particularly in relation to provisioning and regulating ecosystem services. The review identified several determinants that affect farmers’ investments in SWC practices, which are categorized into two groups: (i) factors that are related to farmers’ capacity to invest in SWC practices, and (ii) farmers’ incentives to invest in such practices. Farmers’ investments in SWC are limited by both the capacity to invest and incentives from their investments related to land improvement. The review also showed that farmers’ capacities to invest in SWC practices and their incentives for making such investments have been influenced by external factors, such as institutional support and policies. This suggests that creating enabling conditions for enhancing farmers’ investment capacities in SWC practices, and increasing their incentives for making such investments, is crucial. The review and synthesis showed that the impact of most SWC practices on provisioning ecosystem services (e.g., crop yield) is negative, which is mainly due to the reduction of effective cultivable area due to soil/stone bunds. However, these practices were very effective in regulating ecosystem services, such as soil erosion control, soil fertility improvement and surface runoff reduction.